The development of an authentic speaking material of ESP for basic English learners - Yuli Sintha Asi; Wahyuningsih Usadiati; Elanneri Karani (Journal of Environment and Management, 2021)
Basic Instructional Speaking materials of English for Business Management plays important role in teaching learning process for Economic College in order that the education goal as stipulated in National Framework Curriculum (KKNI) could be achieved. The ability to use English in oral communication is the communicative goal. In fact, there have been many Higher Educations such as Economic College does not provide reliable instructional materials which are based on students‘ needs and industrial needs. Even the materials are not relevant to the students‘ Department. However, since there has no many ESP books and researches done due to this issue, this research was eventually carried out and the final product is to grand a basic instructional material of ESP for Economic Students. The data analyses were through interview and questionnaires to the first grade students of Sekolah Tinggi Ilmu Ekonomi Sampit. The results indicated the students are considered as basic learners of English who need appropriate materials as per their level ability. Therefore, instructional materials for Business English especially for basic learners who want to speak English for Business needs are hardly needed in STIE Sampit.